2012
DOI: 10.1016/j.lingua.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

On the discourse function of particles in post-initial position

Abstract: The paper presents a corpus-based information-structural analysis of the German discourse particles aber and auch in the so-called post-initial position, i.e. between the pre-field constituent and the finite verb in main clauses. Based on corpus data, I argue that aber and auch in this position mark the border between the focus and the background of the sentence that hosts them. By doing this, they essentially contribute to identifying relevant alternatives involved in focus interpretation and discourse interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Of course, the type of "agreement" observable between the topicalized XP, which functions as a clausal frame setter here insofar as it circumscribes the frame (one that is projected into a non-actual world) in which the content of the clause is to be interpreted, and the resumptive does not involve any case and number, but these two elements are referentially identical. 7 In (7c), a contrastive PP frame setter is linearly followed by a socalled "post-initial marker" (Métrich and Courdier 1995;Pasch et al 2003;Breindl 2008;Volodina and Weiß 2010;Karagjosova 2012;Lenker 2014;Catasso 2015;Speyer and Weiß 2018) in the prefield. Post-initial markers are originally adverbial, particle-like elements that systematically surface in second position and accompany a fronted full XP with the function of lexicalizing their information-structural status.…”
Section: What Verb-late(r) Tells Us About Verb Movementmentioning
confidence: 99%
“…Of course, the type of "agreement" observable between the topicalized XP, which functions as a clausal frame setter here insofar as it circumscribes the frame (one that is projected into a non-actual world) in which the content of the clause is to be interpreted, and the resumptive does not involve any case and number, but these two elements are referentially identical. 7 In (7c), a contrastive PP frame setter is linearly followed by a socalled "post-initial marker" (Métrich and Courdier 1995;Pasch et al 2003;Breindl 2008;Volodina and Weiß 2010;Karagjosova 2012;Lenker 2014;Catasso 2015;Speyer and Weiß 2018) in the prefield. Post-initial markers are originally adverbial, particle-like elements that systematically surface in second position and accompany a fronted full XP with the function of lexicalizing their information-structural status.…”
Section: What Verb-late(r) Tells Us About Verb Movementmentioning
confidence: 99%
“…What crucially differentiates between the elements in 12 and focus particles such as sogar is, inter alia, that the former otherwise function as so-called adverbial connectors, while the latter only perform a focusing function. The term (adverbial) connector is generally used in the literature to refer to these items (see, among others, Pasch et al 2003, Ferraresi 2008, Volodina & Weiß 2010, Blühdorn 2012, Karagjosova 2012) However, it seems to me that defining them as connectors when they perform this specific function is misleading, as they do not connect anything, either within the prefield or between two layers (for example, two different CPs or DPs, as a logical connective does). Moreover, in contexts such as 12 they are only homonymous with the corresponding conjunction ( aber ) and nonconjunctional clause-introducing adverbs ( nämlich, nun, schließlich ) 7 .…”
Section: Can the German Prefield Be Multiply-filled?mentioning
confidence: 99%
“…Karagjosova (2012) has shown that focus adverbs may in some cases modify topical information, but han også 'he too' in (9) can clearly designate rhematic information, for instance in a discussion about who needs care.…”
mentioning
confidence: 99%